Resin composition and molded article

The resin composition, comprising a specific thermoplastic resin, heat-storable compound, and porous inorganic compound, addresses the challenges of heat resistance, material leakage, and brittleness in molded bodies, achieving enhanced performance in heat resistance and phase transition effects.

JP7671338B2Active Publication Date: 2025-05-01MITSUI CHEMICALS INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023505161
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-10
Filing Date
2022-01-17
Publication Date
2025-05-01
Estimated Expiration
2042-01-17

AI Technical Summary

Technical Problem

Existing resin compositions containing phase transition materials face challenges with insufficient heat resistance due to low melting points of thermoplastic resins, leakage of phase transition materials, and inadequate brittleness and light weight resistance in molded bodies.

Method used

A resin composition comprising a specific thermoplastic resin, a heat-storable compound with a flash point of 200° C. or higher, and a porous inorganic compound with high oil absorption, which are melt-kneaded at temperatures of 200° C. or higher to produce a molded body with enhanced heat resistance, phase transition effects, and improved brittleness and light weight resistance.

Benefits of technology

The resin composition achieves process heat resistance during high-temperature melt kneading, prevents leakage of phase transition materials, and produces molded bodies with excellent brittleness and light weight resistance, while maintaining effective phase transition effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671338000001
    Figure 0007671338000001
Patent Text Reader

Abstract

The present invention provides: a resin composition which has process heat resistance that is adaptable to the cases where the resin composition is melted and mixed, as a phase transition material, with a resin at a relatively high temperature, and which contains a heat storage compound having characteristics that prevent leakage of the heat storage compound from a resin if formed into a molded body, while enabling the achievement of a molded body that is able to be temperature sensitively controlled, and has excellent embrittlement resistance and excellent lightweight properties; and a molded body which is formed of this resin composition. A resin composition which contains 100 parts by mass of a thermoplastic resin (A) that has a density, an MFR and a type A durometer hardness in specific ranges, 10 to 100 parts by mass of a heat storage compound (B) that has a flash point of 200°C or higher, and 1.5 to 20 parts by mass of a porous inorganic compound (C) that has an oil absorption of 4.0 g / g or more, wherein the content of the heat storage compound (B) is less than 700 parts by mass if the content of the porous inorganic compound (C) is taken as 100 parts by mass.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a molded article, and more particularly to a thermoplastic resin composition capable of controlling the temperature sensation and a molded article thereof. [Background technology]

[0002] Conventionally, there is a concept that by adding a phase-transition material with a large heat capacity to resin, the temperature does not easily change even in the high temperatures of midsummer or the low temperatures of midwinter, and the material does not easily feel hot or cold when touched. This is due to the mechanism that energy is consumed in the phase transition (solid → liquid, liquid → solid) and the temperature is maintained at the phase transition temperature for a certain period of time, making it possible to delay the rise or fall of temperature. Examples based on this concept include sheets that give a cool feeling and materials that suppress the temperature rise of steering wheels and instrument panels that get very hot inside a car in the summer.

[0003] Patent Document 1 discloses a resin composition containing the above-mentioned phase transition material, which is a heat storage resin composition that contains a thermoplastic resin having a heat of crystalline fusion (ΔHm) of 100 J / g or less and heat storage microcapsules, and has a heat of crystalline fusion (ΔHm) of 50 J / g or more.

[0004] Furthermore, Patent Document 2 discloses a resin pellet containing heat storage material particles, which comprises a thermoplastic resin and heat storage material particles dispersed in the thermoplastic resin and containing a heat storage substance, and in which the particle size and other factors of the heat storage material particles satisfy specific conditions. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2019-116570 A [Patent Document 2] JP 2019-218518 A Summary of the Invention [Problem to be solved by the invention]

[0006] Resin compositions containing a phase transition material such as a heat storage compound are required to have high heat resistance depending on the application, but the inventions of Patent Documents 1 and 2 have a problem that the melting point of the thermoplastic resin is not high, and therefore the heat resistance is insufficient. In addition, when a thermoplastic resin with high heat resistance is used, it may be necessary to melt-knead the phase transition material and the thermoplastic resin at a relatively high temperature (for example, a temperature of 200°C or higher), so the phase transition material is required to have heat resistance that can withstand the process temperature when melt-kneading with the resin. In addition, the obtained molded product is required to have the property that the phase transition material does not leak (bleed out) from the resin, as well as brittle resistance and light weight. However, such considerations have not been fully carried out in the prior art.

[0007] The present invention aims to provide a resin composition that contains a heat storage compound as a phase change material that has process heat resistance that can withstand even when melt-kneaded with a resin at relatively high temperatures and has the property of not leaking (bleeding out) from the resin when formed into a molded article, and that allows temperature sensation control to obtain a molded article that is excellent in brittle resistance and light weight, and a molded article made of the resin composition. [Means for solving the problem]

[0008] The present inventors have conducted extensive research to solve the above problems. As a result, they have found that the above problems can be solved by a resin composition containing a specific thermoplastic resin, a heat storage compound, and a porous inorganic compound in specific amounts, and have completed the present invention. Examples of the aspects of the present invention are shown below.

[0009] [1] 100 parts by mass of a thermoplastic resin (A) satisfying the following requirements (a-1) to (a-3); 10 to 100 parts by mass of a heat storage compound (B) (different from the component (A)) having a flash point of 200° C. or higher; 1.5 to 20 parts by mass of a porous inorganic compound (C) having an oil absorption of 4.0 g / g or more; Including, A resin composition, in which the content of the heat storage compound (B) is less than 700 parts by mass when the content of the porous inorganic compound (C) is 100 parts by mass: (a-1) The density, measured in accordance with the method described in ASTM D 1505, is 0.80 to 1.0 g / cm 3 is in the range of; (a-2) The melt flow rate (MFR) measured in accordance with the method described in ISO 1133 at 230°C under a load of 10 kg is in the range of 0.1 to 100 g / 10 min; (a-3) The Durometer A hardness (instantaneous value) measured in accordance with the method described in ISO 7619 is in the range of 30 to 100.

[0010] [2] The resin composition according to item [1], wherein the heat storage compound (B) is a fatty acid ester. [3] The resin composition according to item [1] or [2], wherein the porous inorganic compound (C) is at least one compound selected from the group consisting of silica, alumina, and carbon.

[0011] [4] The resin composition according to any one of items [1] to [3], wherein the oil absorption of the porous inorganic compound (C) is 4.5 g / g or more and 10.0 g / g or less. [5] The resin composition according to any one of items [1] to [4], wherein the porous inorganic compound (C) is hydrophobic silica.

[0012] [6] The resin composition according to any one of items [1] to [5], wherein the heat storage compound (B) has a crystal fusion heat ΔHm of 150 J / g or more. [7] The resin composition according to any one of items [1] to [6], wherein the content of the porous inorganic compound (C) is 1.5 parts by mass or more and less than 14 parts by mass.

[0013] [8] A molded article made of the resin composition according to any one of items [1] to [7]. [9] A method for producing the resin composition according to any one of items [1] to [7], comprising a step of kneading the thermoplastic resin (A), the heat storage compound (B) and the porous inorganic compound (C) at a temperature of 200°C or higher. Effect of the Invention

[0014] The resin composition of the present invention can be produced by melt kneading at a relatively high temperature (for example, a temperature of 200° C. or higher). In addition, by using the resin composition of the present invention, a molded article having the property that the heat storage compound (phase transition material) does not leak (bleed out) from the resin, temperature sensation can be controlled, and it is possible to produce a molded article having excellent brittle resistance and light weight. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention will be described in detail below. [Resin composition] The resin composition according to the present invention comprises: 100 parts by mass of a thermoplastic resin (A) satisfying the requirements (a-1) to (a-3) described below; 10 to 100 parts by mass of a heat storage compound (B) (different from the component (A)) having a flash point of 200° C. or higher; 1.5 to 20 parts by mass of a porous inorganic compound (C) having an oil absorption of 4.0 g / g or more; Including, The present invention is characterized in that the content of the heat storage compound (B) is less than 700 parts by mass when the content of the porous inorganic compound (C) is taken as 100 parts by mass.

[0016] <Thermoplastic resin (A)> The thermoplastic resin (A) used in the present invention satisfies the following requirements (a-1) to (a-3). (a-1) The density, measured in accordance with the method described in ASTM D 1505, is 0.80 to 1.0 g / cm 3 The range is. (a-2) The melt flow rate (MFR), measured in accordance with the method described in ISO 1133 at 230° C. under a load of 10 kg, is in the range of 0.1 to 100 g / 10 min. (a-3) The Durometer A hardness (instantaneous value) measured in accordance with the method described in ISO 7619 is in the range of 30 to 100.

[0017] The density in requirement (a-1) is preferably 0.81 to 0.97 g / cm 3 , more preferably 0.82 to 0.94 g / cm 3 When the density of the thermoplastic resin (A) is within the above range, a molded article having excellent light weight can be obtained.

[0018] The MFR in the requirement (a-2) is preferably 0.5 to 80 g / 10 min, more preferably 1 to 50 g / 10 min. When the MFR of the thermoplastic resin (A) is within the above range, the moldability of the resulting resin composition is excellent.

[0019] The Durometer A hardness (instantaneous value) in requirement (a-3) is preferably 40 to 90, more preferably 40 to 85, and further preferably 40 to 80. When the Durometer A hardness (instantaneous value) of the thermoplastic resin (A) is within the above range, embrittlement is unlikely to occur even if the porous inorganic compound (C) is added within the specified range.

[0020] The thermoplastic resin (A) as described above is not particularly limited as long as it satisfies the above requirements (a-1) to (a-3), and examples thereof include olefin resins, styrene resins, acrylic resins, polyester resins, polyvinyl chloride resins, polyamide resins, polycarbonate resins, polylactic acid resins, polyimide resins, polysulfone resins, and aromatic polyketone resins. These resins can be used alone or in combination of two or more, and commercially available products may be used. Among the above, olefin resins are preferred, and olefin thermoplastic elastomers are more preferred.

[0021] A preferred example of the olefin-based thermoplastic elastomer is a dynamically crosslinked product of ethylene-α-olefin-non-conjugated polyene copolymer [I] having 3 to 20 carbon atoms (hereinafter also referred to as "ethylene-α-olefin-non-conjugated polyene copolymer [I]") and polyolefin resin [II].

[0022] The dynamically crosslinked product may be obtained by dynamically crosslinking one kind of ethylene-α-olefin-non-conjugated polyene copolymer [I] or one kind of polyolefin resin [II], or may be obtained by dynamically crosslinking a plurality of ethylene-α-olefin-non-conjugated polyene copolymers [I] or a plurality of polyolefin resins [II].

[0023] In this specification, dynamic crosslinking means that the ethylene-α-olefin-non-conjugated polyene copolymer [I] and the polyolefin resin [II] are kneaded in a molten state to crosslink at least a portion of the carbon-carbon double bonds in the ethylene-α-olefin-non-conjugated polyene copolymer [I].

[0024] Ethylene-α-olefin-non-conjugated polyene copolymer[I] The ethylene-α-olefin-non-conjugated polyene copolymer [I] contains a structural unit (a) derived from ethylene, a structural unit (b) derived from an α-olefin having 3 to 20 carbon atoms, and a structural unit (c) derived from a non-conjugated polyene.

[0025] The molar ratio (a) / (b) of the constituent unit (a) to the constituent unit (b) in the ethylene / α-olefin / non-conjugated polyene copolymer [I] is preferably 50 / 50 to 95 / 5, more preferably 60 / 40 to 80 / 20, and even more preferably 65 / 35 to 75 / 25.

[0026] On the other hand, the specific amount of the constitutional unit (c) derived from the non-conjugated polyene in the ethylene-α-olefin-non-conjugated polyene copolymer [I] is preferably 2 to 20 mass % based on the total amount of the ethylene-α-olefin-non-conjugated polyene copolymer [I].

[0027] Specific examples of the α-olefin having 3 to 20 carbon atoms constituting the ethylene-α-olefin-non-conjugated polyene copolymer [I] include propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-nonadecene, 1-eicosene, 9-methyl-1-decene, 11-methyl-1-dodecene, 12-ethyl-1-tetradecene, and the like.

[0028] Among them, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene are preferable The ethylene-α-olefin-non-conjugated polyene copolymer [I] may contain only one type of α-olefin-derived structural unit (b), or may contain two or more types.

[0029] The non-conjugated polyene constituting the ethylene-α-olefin-non-conjugated polyene copolymer [I] may be a compound that does not have a conjugated structure and has two or more carbon-carbon double bonds. Specific examples thereof include linear non-conjugated dienes such as 1,4-hexadiene, 3-methyl-1,4-hexadiene, 4-methyl-1,4-hexadiene, 5-methyl-1,4-hexadiene, 4,5-dimethyl-1,4-hexadiene, 7-methyl-1,6-octadiene, 8-methyl-4-ethylidene-1,7-nonadiene, and 4-ethylidene-1,7-undecadiene; methyltetrahydroindene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, and 5-isopropylidene-2-nonadiene; cyclic non-conjugated dienes such as norbornene, 5-vinylidene-2-norbornene, 6-chloromethyl-5-isopropenyl-2-norbornene, 5-vinyl-2-norbornene, 5-isopropenyl-2-norbornene, 5-isobutenyl-2-norbornene, cyclopentadiene, and norbornadiene; 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, 2-propenyl-2,2-norbornadiene, 4-ethylidene-8-methyl-1,7- Nona and trienes such as dienes.

[0030] Among these non-conjugated polyenes, 5-ethylidene-2-norbornene (ENB) and 5-vinyl-2-norbornene (VNB) are particularly preferred. The ethylene-α-olefin-non-conjugated polyene copolymer [I] may contain only one type of non-conjugated polyene-derived structural unit (c), or may contain two or more types.

[0031] The ethylene-α-olefin-non-conjugated polyene copolymer [I] may be so-called oil-extended rubber, which is prepared by blending a softener, preferably a mineral oil-based softener, during its production. The mineral oil-based softener may be a conventionally known mineral oil-based softener, and examples thereof include paraffin-based process oil.

[0032] The ethylene-α-olefin-non-conjugated polyene copolymer [I] can be produced by a conventionally known method.

[0033] Polyolefin resin [II] The polyolefin resin [II] may be any polyolefin-based resin that does not substantially have an unsaturated bond in the main chain. Specific examples thereof include homopolymers of α-olefins such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, and 1-decene; and copolymers thereof. When the polyolefin resin [II] is a copolymer, it is preferable that the content of any one of the α-olefins is 90 mol% or more.

[0034] In particular, the polyolefin resin [II] is preferably a propylene-based polymer (II-1) containing propylene as a main component, or an ethylene-based polymer (II-2) containing ethylene as a main component.

[0035] Examples of the propylene polymer (II-1) include a propylene homopolymer, a random copolymer of propylene and an α-olefin having 2 to 10 carbon atoms (e.g., ethylene, 1-butene, 1-pentene, 4-methyl-1-pentene, etc.), a block copolymer of a propylene homopolymer and an amorphous or low-crystalline propylene-ethylene random copolymer, etc. However, the amount of structural units other than propylene is preferably 10 mol % or less based on the total amount of structural units.

[0036] The propylene polymer (II-1) may be one polymerized by a known polymerization method, or may be one that is manufactured and sold as a polypropylene resin.

[0037] Furthermore, the propylene polymer (II-1) preferably has an isotactic stereostructure, but may have a syndiotactic structure, a mixture of these structures, or may partially contain an atactic structure.

[0038] On the other hand, examples of the ethylene polymer (II-2) include ethylene homopolymers and random copolymers of ethylene and an α-olefin having 3 to 10 carbon atoms (e.g., propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, etc.). In the ethylene polymer (II-2), the amount of structural units other than ethylene is preferably 10 mol % or less based on the total amount of structural units.

[0039] The ethylene polymer (II-2) may be one polymerized by a known polymerization method, or may be one manufactured and sold as high-pressure low-density polyethylene, linear low-density polyethylene, high-density polyethylene, or the like.

[0040] Method for preparing dynamic crosslinked bodies The dynamically crosslinked product can be prepared by adding the above-mentioned ethylene-α-olefin-non-conjugated polyene copolymer [I] and polyolefin resin [II], and, if necessary, a known crosslinking agent, crosslinking assistant, and softener, and kneading (dynamic crosslinking). Commercially available products may also be used. When dynamically crosslinking, either a closed type device or an open type device may be used, but it is preferable to use a closed type device.

[0041] The dynamic crosslinking is preferably carried out under an atmosphere of an inert gas such as nitrogen or carbon dioxide. The temperature during dynamic crosslinking is usually in the range of from the melting point of the polyolefin resin [II] to 300°C, preferably 150 to 270°C, more preferably 170 to 250°C. The kneading time is preferably 1 to 20 minutes, more preferably 1 to 10 minutes. The shear rate at this time is preferably 10 to 50,000 sec. -1 , more preferably 100 to 20,000 sec -1 It is.

[0042] Examples of kneading devices used for dynamic crosslinking include mixing rolls, intensive mixers (eg, Banbury mixer, kneader), single-screw or twin-screw extruders, etc., with non-open type devices being preferred, and twin-screw extruders being particularly preferred.

[0043] <Heat storage compound (B)> The heat storage compound (B) used in the present invention is used as a phase transition material and is a compound having a flash point of 200° C. or higher, preferably 210° C. to 300° C., more preferably 220° C. to 290° C., and even more preferably 220° C. to 280° C. (provided that it is a compound other than the component (A)). By having a flash point within the above range, it can be incorporated into the resin composition without thermal decomposition even when melt-kneaded with the component (A) etc. at high temperatures of 200° C. or higher, and an excellent phase transition effect can be exhibited.

[0044] The heat of crystal fusion ΔHm of the heat storage compound (B) is preferably 150 J / g or more, more preferably 180 J / g or more and 300 J / g or less, further preferably 210 J / g or more and 290 J / g or less, and particularly preferably 210 J / g or more and 280 J / g or less. When the heat of crystal fusion ΔHm of the heat storage compound (B) is within the above range, the above-mentioned effects are enhanced.

[0045] Examples of the heat storage compound (B) include compounds having a non-bulky chain structure that does not contain cyclic or multiple bonds, a structure having a hydrocarbon, a structure having a hydrogen bond unit such as a carbonyl group or a hydroxyl group, etc. More specifically, fatty acid esters, aliphatic alcohols, fatty acids, etc. are included, and among these, fatty acid esters are preferred, and fatty acid esters in which the substituents on both ends of the ester are chain-like are more preferred.

[0046] Examples of fatty acid esters include isocetyl myristate, octyldodecyl myristate, isocetyl isostearate, cetyl 2-ethylhexanoate, isocetyl stearate, 2-ethylhexyl palmitate, isotridecyl stearate, butyl stearate, dodecyl stearate, myristyl myristate, cetyl myristate, hexadecyl palmitate, stearyl stearate, docosyl docosanoate, etc. Among these, stearyl stearate, myristyl myristate, cetyl myristate, and docosyl docosanoate are preferred.

[0047] The aliphatic alcohol is preferably one having 20 or more carbon atoms, for example, behenyl alcohol, and the fatty acid is preferably one having 20 or more carbon atoms, for example, behenic acid.

[0048] The heat storage compound (B) can be appropriately selected depending on the desired phase transition temperature (heat retention temperature), and one type may be used alone, or two or more types may be used in combination.

[0049] <Porous inorganic compound (C)> The oil absorption of the porous inorganic compound (C) used in the present invention is 4.0 g / g or more, preferably 4.5 g / g to 10.0 g / g, more preferably 5.0 g / g to 9.5 g / g, and even more preferably 5.0 g / g to 9.0 g / g. When the oil absorption of the porous inorganic compound (C) is within the above range, it is possible to retain a larger amount of the heat storage compound (B), and therefore it is possible to suppress bleeding out of the heat storage compound (B) from the resin when the molded product is produced.

[0050] The average particle size of the porous inorganic compound (C) is preferably 1 μm or more and 100 μm or less. The average particle size of the porous inorganic compound (C) is within the above range, and thereby the above-mentioned effects are enhanced. The average particle size is a value measured by an apparatus and an analysis method suitable for the particle size, for example, a value measured by a laser diffraction / scattering method.

[0051] The porous inorganic compound (C) is not particularly limited as long as it is a porous inorganic compound having the above-mentioned oil absorption amount, but from the viewpoint of having excellent heat resistance, for example, silica, alumina, carbon, etc. can be mentioned. These can be used alone or two or more kinds can be used. Among them, silica is preferred, and from the viewpoint of being able to further enhance the oil absorption effect, hydrophobic silica is more preferred.

[0052] In addition, the porous inorganic compound (C) is preferably one that is less likely to volatilize and ignite when the heat storage compound (B) is held in the porous inorganic compound (C) and the temperature is equal to or higher than the melting point (melting peak temperature) of the heat storage compound (B) compared to when the heat storage compound (B) is a single substance. Examples of such a preferable porous inorganic compound (C) include THIL L One example is "AEROS" manufactured by IUM.

[0053] <Composition> The content of each component in the resin composition of the present invention is, relative to 100 parts by mass of the thermoplastic resin (A), The content of the heat storage compound (B) is 10 to 100 parts by mass, preferably 12 to 80 parts by mass, and more preferably 15 to 50 parts by mass. The content of the porous inorganic compound (C) is 1.5 to 20 parts by mass, preferably 2.0 to 18 parts by mass, and more preferably 2.5 to 16 parts by mass. The content of the porous inorganic compound (C) can also be 1.5 parts by mass or more and less than 14 parts by mass, 2.0 parts by mass or more and less than 14 parts by mass, or 2.5 parts by mass or more and less than 14 parts by mass.

[0054] Furthermore, when the content of the porous inorganic compound (C) is 100 parts by mass, the content of the heat storage compound (B) is less than 700 parts by mass, preferably 100 parts by mass or more and less than 700 parts by mass, and more preferably 200 parts by mass or more and less than 700 parts by mass.

[0055] By ensuring that the content of each component satisfies the above conditions, when a molded article is produced, the heat storage compound (B) does not leak out (bleed out) from the resin, a sufficient phase transition effect is obtained, and a molded article having excellent brittle resistance and light weight can be obtained.

[0056] <Optional ingredients> In addition to the above-mentioned components (A) to (C), the resin composition of the present invention may contain additives such as slip agents, nucleating agents, fillers, antioxidants, weather stabilizers, colorants (including thermochromic materials), foaming agents, pigments, dyes, antistatic agents, and flame retardants as optional components within the scope of the present invention.

[0057] <Method of producing resin composition> The method for producing the resin composition of the present invention includes a step of kneading the thermoplastic resin (A), the heat storage compound (B), the porous inorganic compound (C), and optional components as required, at a temperature of 200° C. or higher, preferably 210° C. or higher and 300° C. or lower, more preferably 220° C. or higher and 260° C. or lower. The kneading time is usually 1 to 20 minutes, preferably 1 to 10 minutes.

[0058] As the kneading device, a mixing roll, an intensive mixer (for example, a Banbury mixer, a kneader), a single-screw or twin-screw extruder, etc. can be used, but a non-open type device is preferred.

[0059] [Molded body] The molded article of the present invention is made of the resin composition of the present invention described above. As the molding method, various known methods can be adopted. Specifically, extrusion molding, press molding, injection molding, calendar molding, blow molding, etc. can be mentioned. In addition, the molded article such as a sheet obtained by the above molding method can be secondary processed by thermoforming, etc., or laminated with other materials to form a molded article.

[0060] The uses of the molded article of the present invention are not particularly limited, and it is suitable for various known uses such as automobile parts, civil engineering and building materials, electric and electronic parts, sanitary products, films and sheets, foams, etc. In particular, it is also useful as a material for steering wheels and instrument panels that become hot inside a car in summer, wearable materials, apparel materials, shoes, various types of cooling materials, cooling containers, heat insulation materials, and heat insulation containers. EXAMPLES

[0061] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0062] [material] The components of the resin compositions produced in the examples and comparative examples are as follows. <Thermoplastic resin> A-1: "Milastomer 6010NST" manufactured by Mitsui Chemicals, Inc. (a cross-linked thermoplastic elastomer mainly composed of olefin-based rubber (EPT) and olefin-based resin (PP), density: 0.88 g / cm 3 , MFR (230℃, 10kg load): 12g / 10min, Durometer A hardness (instantaneous value): 70) A'-2: Polyvinyl chloride (density: 1.2g / cm 3 , Durometer A hardness (instantaneous value): 70)

[0063] <Heat storage compounds (phase change materials)> B-1: Kao Corporation's "Exepar SS" (stearyl stearate, flash point: 258°C, ΔHm: 234J / g) B-2: Kao Corporation "Exepar MY-M" (myristyl myristate, flash point: 239°C, ΔHm: 229J / g) B-3: NOF Corp. "Sperm Acetate" (cetyl myristate, flash point: 228°C, ΔHm: 241J / g) B-4: NOF Corp. "Unistar M-2222SL" (docosyl docosanoate, flash point: 270°C, ΔHm: 224J / g) B'-5: "Octadecane" manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. (Flash point: 154°C) B'-6: Melamine capsule "PMCD-28SP" manufactured by Miki Riken Kogyo Co., Ltd. (Flash point: 160°C)

[0064] <Porous inorganic materials> ·C-1: Hydrophobic silica (THIL) L "AEROS" manufactured by IUM, oil absorption: 7g / g) ·C'-2: Activated carbide ("Sumirei" manufactured by Taniguchi Shokai Co., Ltd., oil absorption: 3.4g / g)

[0065] [Examples 1 to 6 and Comparative Examples 1 to 14] The amounts (parts by mass) of thermoplastic resin, heat storage compound (phase transition material), and porous inorganic material shown in Table 1 were kneaded for 5 minutes using a Labo Plastomill ("80C100" manufactured by Toyo Seiki Seisakusho Co., Ltd.) at a temperature of 240°C and a torque rotation speed of 30 rpm. After kneading, the kneaded product was promptly collected. The kneaded product obtained was cut into small pieces with scissors, approximately 0.5 cm x 0.5 cm x 0.5 cm in size.

[0066] A Teflon (registered trademark) sheet and a mold were placed in that order on a stainless steel plate (hereinafter also referred to as "SUS plate"), and the cut pieces obtained above were laid out in the holes of the mold. After the cut pieces were laid out, the Teflon (registered trademark) sheet and the SUS plate were stacked in that order. The Teflon (registered trademark) sheet was used to prevent the kneaded material from sticking to the SUS plate during heat pressing. The above molds were 6.5 cm long, 6.5 cm wide, and three types of thickness (1 mm, 2 mm, and 5 mm) were used.

[0067] The obtained laminate was hot-pressed for 5 minutes at a temperature of 240°C and a pressure of 10 MPa using a compression molding machine ("ASF-10" manufactured by Shinto Metal Industries Co., Ltd.). After that, while sandwiched between SUS plates, it was quickly transferred to a compression molding machine ("NSF-37" manufactured by Shinto Metal Industries Co., Ltd.) and cooled for 5 minutes at a pressure of 10 MPa. After cooling, the SUS plates and Teflon (registered trademark) sheet were removed from the mold to obtain a hot-pressed sheet sample having the thickness shown in Table 1. The produced hot-pressed sheet samples were evaluated as follows.

[0068] <Bleed out> The top and bottom of the heat-pressed sheet sample obtained above was sandwiched between clean paper so that the 6.5 cm x 6.5 cm surface and the clean paper were parallel, and then the top and bottom were further sandwiched between SUS plates, and then heat-pressed for 5 minutes at a temperature of 100 ° C and a pressure of 10 MPa using a compression molding machine ("ASF-10" manufactured by Shinto Metal Industry Co., Ltd.). After heat pressing, the heat-pressed sheet sample was quickly peeled off from the clean paper. The condition of the clean paper was checked, and if there was no mark on the area where the sheet was placed, it was evaluated as "〇: no leakage", and if there was a mark, it was evaluated as "×: leakage".

[0069] <Brittleness resistance> The heat-pressed sheet sample obtained above was cut to a size of 1.0 cm in length and 6.5 cm in width to prepare a test piece for a tensile test, and the tensile elongation of the test piece was measured using a Tensilon universal testing machine (model: RTG-1225) at a tensile speed of 300 mm / min and a chuck distance of 50 mm. The tensile elongation value at the time when the test piece broke was calculated as elongation rate (%) = elongation value (mm) / chuck distance (mm), and the test piece was evaluated based on the measured elongation rate according to the following criteria. ○: Greater than 10% △: 5~10% ×: Less than 5%

[0070] <Heat retention> About 5 mg was cut out from the heat-pressed sheet sample obtained above, and measurement was performed using a differential scanning calorimeter (DSC) under the following conditions. Measurement device: X-DSC7000 (SII) Temperature: Start from -40℃, increase to 100℃, hold at 100℃ for 1 minute, then decrease to -40℃ Heating rate and cooling rate: 3℃ / min Measurement atmosphere: Nitrogen Pretreatment: None Pan: Simple sealed pan

[0071] From the melting peak obtained by the measurement, information on the melting enthalpy ΔH (J / g) of the heat storage compound (phase transition material) was obtained. Based on the obtained ΔH value, evaluation was made according to the following criteria. 〇: Greater than 50 J / g △: 25~50J / g ×: Less than 25 J / g

[0072] <Lightweight> The weight of the heat-pressed sheet sample obtained above was measured with a precision balance, and the weight was divided by the volume of the heat-pressed sheet obtained to obtain the density. Based on the obtained density value, the following criteria were used for evaluation. 〇:0.9g / cm 3 less than △: 0.9g / cm 3 More than 1g / cm 3 less than ×:1g / cm 3 End

[0073] <Overall rating> If there was at least one × in the above evaluations, the overall evaluation was marked × (not suitable).

[0074] [Table 1]

[0075] Examples 1 to 6 were given an overall rating of "○", but all of the comparative examples were given a rating of "×". In Comparative Examples 13 and 14, the heat storage compound (phase transition material) volatilized when preparing the heat-pressed sheet sample, and the heat-pressed sheet sample could not be prepared and evaluated, so the overall rating was also given as "×".

Claims

1. 100 parts by mass of a thermoplastic resin (A) satisfying the following requirements (a-1) to (a-3); 10 to 100 parts by mass of a fatty acid ester (B) (different from the component (A)) having a flash point of 200° C. or higher; 1.5 to 20 parts by mass of a porous inorganic compound (C) having an oil absorption of 4.0 g / g or more; Including, The content of the fatty acid ester (B) is less than 700 parts by mass when the content of the porous inorganic compound (C) is 100 parts by mass, the thermoplastic resin (A) comprises a dynamically crosslinked product of an ethylene-C3-C20 α-olefin-non-conjugated polyene copolymer [I] and a polyolefin resin [II]; A resin composition, wherein the porous inorganic compound (C) contains silica: (a-1) The density measured in accordance with the method described in ASTM D 1505 is 0.80 to 1.0 g / cm 3 is in the range of (a-2) The melt flow rate (MFR) measured at 230°C under a load of 10 kg in accordance with the method described in ISO 1133 is in the range of 0.1 to 100 g / 10 min; (a-3) The durometer A hardness (instantaneous value) measured in accordance with the method described in ISO 7619 is in the range of 30 to 100.

2. The resin composition according to claim 1, wherein the oil absorption of the porous inorganic compound (C) is 4.5 g / g or more and 10.0 g / g or less.

3. The resin composition according to any one of claims 1 to 2, wherein the porous inorganic compound (C) is hydrophobic silica.

4. The resin composition according to any one of claims 1 to 3, wherein the fatty acid ester (B) has a crystal fusion heat ΔHm of 150 J / g or more.

5. The resin composition according to any one of claims 1 to 4, wherein the content of the porous inorganic compound (C) is 1.5 parts by mass or more and less than 14 parts by mass.

6. A molded article made of the resin composition according to any one of claims 1 to 5.

7. A method for producing the resin composition according to any one of claims 1 to 5, comprising the step of kneading a thermoplastic resin (A), a fatty acid ester (B), and a porous inorganic compound (C) at a temperature of 200°C or higher.

Citation Information

Patent Citations

  • Fire-retardant phase transfer cementitious composite

    JP1990026884A

  • Polyolefin composite containing phase transition substance

    JP1990036235A

  • Thermoplastic elastomer resin composition

    JP2016196601A

  • Heat storage resin composition, manufacturing method therefor and molded body

    JP2019116570A

  • Thermal storage material particle-containing resin pellet, and manufacturing method of thermal storage material particle-containing resin pellet

    JP2019218518A